Rupture Between Promises, Will and Autonomy: What Justifies the Binding Force of the Contract? - Pereira Fredes, Esteban Antonio (2022)
This paper aims to show that the binding force of the contract is justified in respect for the personal autonomy of the contracting parties. To do this, a contrast is made between the notions of will, promises and autonomy that have led the efforts to justify the binding effect of the contract in dogmatic and philosophical studies of contract law. Finally, some advantages of personal autonomy over other competing parameters are indicated, reinforcing its relevance to support the principle pacta sunt servanda.